“Steve, you must feel pig sick!”: Streamed Video Interactions between Premier League Managers and Sports Journalists as Semi-scripted Performances - Heaney, Dermot (HERMES - Journal of Language and Communication in Business, 2011)
The starting point of this paper is the phenomenon of so-called MediaSport, namely the pervasive and multi-faceted mediation of sports events that extends the reach and hold of the sports industry on communities of sports consumers. The speciﬁc aspect of MediaSport considered here is the streamed post-match interview with Premier League team managers, a stabilized media interaction that reﬂects the importance of media duties as part of the manager’s corporate brief. Critical attention to managers seems mainly conﬁned to sociological studies of the politics of celebrity, while linguists seemingly have little to say about this kind of discourse. The data selected for analysis are two interviews following defeat. The choice falls on this scenario because it is expected it will entail a greater onus on managers to display media interaction expertise. Using a theoretical framework that draws on Goffman’s concepts of performance, participation framework, and face, the discourse analysis in this paper attempts to provide an account of the linguistic resources managers draw on in these mediated interactions. The analysis of turn-taking, topic control, deixis and modality reveals similarities in the sample interviews that suggest these encounters are actually semi-scripted collaborative performances that allow both interactants to preserve their face as competent professionals, while also affording the manager ample opportunity to interact with the major imagined recipient, namely, the online fan base.